PAI Teachers' Efforts in Strengthening the Value of Tasamuh Grade 7 at SMP It Sains Al-Biruni Bandung Qualitative Study on the Implementation of Mentoring - Wulandari, Putri; Supala; Fadhli, Rahmat; Chadidjah, Sitti; Fadlani Salam, Mochamad (Zona Education Indonesia, 2025)
The efforts of PAI teachers in strengthening the values of tasamuh conducted by PAI teachers at SMP IT Sains Al Biruni are implemented through a mentoring program. This is necessary because there is still a lack of mutual respect and appreciation among students in the environment of SMP IT Sains Al Biruni Bandung, especially in the 7th grade. Although this school is based on Islamic values and all students are Muslim, there are still verbal conflicts and attitudes that indicate that the values of tasamuh (tolerance) have not been fully instilled. One of the ways teachers strengthen character in this school is through a mentoring program that is carried out routinely once a week on Mondays. The aim of this research is to understand students' comprehension of the value of tolerance, to identify the efforts of PAI teachers in strengthening the value of tolerance, to understand the implementation of the mentoring program in reinforcing the value of tolerance, and to know the supporting and inhibiting factors. This research uses a descriptive-analytical qualitative approach. The data collection methods utilized include observation, interviews, and documentation techniques. Furthermore, the analysis techniques performed are data reduction, data presentation, and conclusion drawing. Based on the research results, it shows that 1) The understanding of 7th-grade students regarding the values of tolerance is quite good, but its application still requires guidance; 2) The Islamic Education (PAI) teacher plays a very active role through exemplary behavior, personal approaches, and contextual learning in strengthening tolerance values; 3) The mentoring program serves as the main effective medium for the internalization of tolerance values through discussions, reflections, and emotional guidance; 4) Supporting factors include the commitment of teachers and school principals, supporting facilities, and a humanistic approach, while the inhibiting factors include the emotional instability of students, a lack of support from family environments, and limited time for mentoring implementation, the lack of support from the family environment, and the limited time for mentoring implementation